2008
DOI: 10.1007/s12630-008-9016-3
|View full text |Cite
|
Sign up to set email alerts
|

The protective effects of emulsified isoflurane on myocardial ischemia and reperfusion injury in rats

Abstract: Purpose Pretreatment with volatile anesthetics has been demonstrated to exert cardioprotective effects. The purpose of this study was to examine the effect of emulsified isoflurane, a new formulation of isoflurane in lipid emulsion, administered intravenously in an ischemia and reperfusion model of myocardial injury. Methods Thirty-two Sprague Dawley rats of both sexes were subjected to 30 min of myocardial ischemia followed by 180 min of reperfusion. Each was assigned to one of four pretreatment groups to rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
27
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 39 publications
(43 reference statements)
4
27
0
Order By: Relevance
“…EIso, an innovative formation of isoflurane, that enables an intravenous (rather than the traditional inhalation) route of administration for this anesthetic (5, 6), was shown to have similar cardioprotective effect as isoflurane does. For example, we and other researches have demonstrated that intravenous infusion of EIso could produce acute and delayed preconditioning or postconditioning against myocardial infarction in animals (7)(8)(9)(10)(11)(12). The current results also confirmed these previous findings demonstrating that in a rat model of severe burn injury, EIso could also protect hearts by decreasing serum levels of SOD and MDA and attenuating decreases in LVSP and dP/dtmax 2 to 3 hours post burn injury.…”
Section: Discussionsupporting
confidence: 89%
“…EIso, an innovative formation of isoflurane, that enables an intravenous (rather than the traditional inhalation) route of administration for this anesthetic (5, 6), was shown to have similar cardioprotective effect as isoflurane does. For example, we and other researches have demonstrated that intravenous infusion of EIso could produce acute and delayed preconditioning or postconditioning against myocardial infarction in animals (7)(8)(9)(10)(11)(12). The current results also confirmed these previous findings demonstrating that in a rat model of severe burn injury, EIso could also protect hearts by decreasing serum levels of SOD and MDA and attenuating decreases in LVSP and dP/dtmax 2 to 3 hours post burn injury.…”
Section: Discussionsupporting
confidence: 89%
“…These data support a cardioprotective effect of intravenous emulsified isoflurane against myocardial ischemia and reperfusion injury, which are mediated, at least in part, by the inhibition of apoptosis and cell damage [8]. It has been shown that inhaled isoflurane limits the size of myocardial infarcts.…”
Section: Emulsified Isoflurane (Eiso)supporting
confidence: 62%
“…More recently, studies reported that preconditioning with emulsified isoflurane protects the hepatocyte and myocardium against I/R injury [10e13]. The mechanisms probably involved are the inhibition of cell death and improvement of the mitochondrial function [11,12]. Evidence indicates that emulsified isoflurane may be as effective as isoflurane in protecting the organs.…”
Section: Introductionmentioning
confidence: 99%